FRI0578 LACC1 MUTATION IN THREE SIBLINGS WITH POLYARTHRITIS WITHOUT SYSTEMIC MANIFESTATIONS. (June 2019) - Singh, Ankita; Suri, Deepti; Jacob, Prince; Girisha, Katta Mohan; Jindal, Ankur; Singh, Surjit
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a complex group of disorders characterized by wide phenotypic diversity and genetic heterogeneity. It has multifactorial etiology varying among different subtypes. There are emerging reports on new gene loci being identified especially in families with many affected members (1, 2) Objectives: To report 3 siblings with polyarthritis who were detected to have mutation in Laccase domain containing 1 ( LACC 1 ) gene. Methods: We reviewed case records of 3 siblings with infantile onset polyarthritis and performed whole exome sequencing on their DNA samples for LACC1, MMP2 and WISP genes. Results: A non-consanguineous family from north-western part of India reported with 3 daughters having polyarticular joint disease. The chronology of symptoms was similar in all 3 children. Joint symptoms started in later half of infancy with swelling of knee and ankle. This disease was progressive and over the following 2 years there was involvement of small joints and cervical spine too (Figure 1) along with deformities and contractures. The investigations at the time of first evaluation are given in Table 1. Radiographs in all 3 sisters showed osteoporosis and erosion of vertebrae (Figure 2). The children were initially started on naproxen. Later, in view of rheumatoid factor positivity in eldest sister we decided to give them a trial of oral prednisolone (initially 1 mg/kg and subsequently tapered) and subcutaneous methotrexate (10 mg/m 2 /week). Methotrexate was continued on long term basis. Over the next 24 months of follow-up the clinical improvement has been sustained. Whole-exome-sequencing in all three girls has revealed mutation in LACC1 gene [Exon 4; c.832G>C; p.(Ala278Pro), Homozygous, Autosomal recessive]. Conclusion: This case report further provides evidence to the emerging association of LACC1 mutation with familial aggregation of JIA (1, 2). Long term follow-up of these patients is necessary to determine the natural course of this intriguing clinical entity. References: [1] Wakil SM, Monies DM, Abouelhoda M, Al-Tassan N, Al-Dusery H, Naim EA, et al. Association of a Mutation in LACC1With a Monogenic Form of Systemic Juvenile Idiopathic Arthritis: Monogenic Systemic Juvenile Idiopathic Arthritis. Arthritis & Rheumatology. 2015Jan;67(1):288–95. [2] Karacan I, Uğurlu S, Şahin S, Everest E, Kasapçopur Ö, Tolun A, et al. LACC1 Gene Defects in Familial Form of Juvenile Arthritis. J Rheumatol. 2018May;45(5):726–8. Disclosure of Interests: None declared